Ethanolic Extract of the Leaf of Moringa oleifera Lam. as a Potential Anthelmintic Agent Against Gastrointestinal Nematodes in Goats - Pandey, Arjun; Neupane, Sabina; Prasai, Ullash; Thapaliya, Sharada; Shah, Manoj K. (Journal of Agriculture and Forestry University, 2026)
Moringa oleifera Lam. has been used in different countries to treat parasitic infections in humans and livestock. This study was aimed to investigate the anthelminthic activity of ethanolic extract of Leaf of Moringa oleifera Lam. (EEMO) against gastrointestinal nematodes in goats. EEMO was prepared in 100% ethanol by cold percolation and qualitative tests were performed for phytochemical screening. Forty male goats (Egg Per Gram/EPG at least 100) were randomly selected and allocated equally into Negative control (N-Ctrl), Moringa oleifera ethanolic extract (MO-100), MO-200 and Positive control (P-Ctrl). The goats of MO-100, MO- 200 and P-Ctrl groups received orally MO extract @ 100 mg/kg, 200 mg/kg and albendazole 10 mg/kg body weight, respectively whereas normal water was provided to the goats of N-Ctrl group. EPG count was assessed by Mc-Master technique followed by FECR% (Fecal egg count reduction percentage) on day 0, 3, 7, 14 and 28. Phytochemical screening revealed the presence of saponin and flavonoid. EPG decreased and FECR% increased in both extracts treated groups on the dose dependent manner on day 7-28. The highest FECR% were observed with MO-100 (77.03±7.54) and MO-200 (91.83±2.26) on day 28. Therefore, our study has shown that MO @ 200 mg/kg has sufficient anthelmintic activity against gastrointestinal nematodes in goat.